Influence of elastic anisotropy on the mechanical behavior of soils. Issue 9 (4th July 2022) - Hu, Lian Xin; Prunier, Florent; Daouadji, Ali
Abstract: The mechanical behavior of soils can be modeled using a non-linear elastic part showing an incremental response depending on current stress state, while the plastic part can be described appropriately by a smoothed Drücker-Prager based plastic criterion. In order to reproduce the behavior of such media under prescribed loading, a new constitutive model is proposed as a combination of a hyperelastic formulation and a plastic criterion within the elastoplasticity framework. In this new model, both inherent and induced anisotropies are taking into account in the elastic part by mean of a pressure exponent parameter. The tangent stiffness matrix of the elastoplastic model varies as a function of current state of stress which is in accordance with experimental observations of soils and leads to define only one set of parameters for the different initial mean stresses. It is found that the stress-strain responses including hardening tendencies are affected by different values of the pressure exponent which accords to different levels of anisotropy, and the level of influence of anisotropy is related with density and the drainage condition of soils.